2000
DOI: 10.1046/j.1365-2958.2000.0err2.x
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the gene (cpe) encoding Clostridium perfringens enterotoxin eliminates the ability of two cpe‐positive C. perfringens type A human gastrointestinal disease isolates to affect rabbit ileal loops

Abstract: The authors of this article, which was published in Mol Microbiol (1999) 33 (5): 946-958, would like to apologize for the omission of the following in the Acknowledgements section: 'The authors also wish to thank Dr Stephen Melville, University of Tennessee School of Medicine, Memphis, TN, USA, for the generous gift of C. perfringens strain SM101. ' In addition, in recognition of this gift, they would like to add the following amendments to their text. On page 947, the first sentence of the first paragraph … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
59
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(59 citation statements)
references
References 20 publications
0
59
0
Order By: Relevance
“…Some earlier in vivo studies using CPE-treated rabbit ileal loops observed inflammatory cell (mostly PMNs) infiltration (McDonel et al 1978), while other studies using the same in vivo model failed to detect any CPE-induced inflammation (Sarker et al 1999;Sherman et al 1994). The presence or absence of inflammatory cell infiltration in those rabbit ileal loop experiments appeared to be CPE dose-dependent, with inflammation more prominent in the ileal loops treated with high CPE doses (McDonel and Duncan 1975).…”
Section: Cpe-induced Cellular Death Pathwaysmentioning
confidence: 98%
See 3 more Smart Citations
“…Some earlier in vivo studies using CPE-treated rabbit ileal loops observed inflammatory cell (mostly PMNs) infiltration (McDonel et al 1978), while other studies using the same in vivo model failed to detect any CPE-induced inflammation (Sarker et al 1999;Sherman et al 1994). The presence or absence of inflammatory cell infiltration in those rabbit ileal loop experiments appeared to be CPE dose-dependent, with inflammation more prominent in the ileal loops treated with high CPE doses (McDonel and Duncan 1975).…”
Section: Cpe-induced Cellular Death Pathwaysmentioning
confidence: 98%
“…More recently, molecular Koch's postulates analyses using an isogenic cpe mutant of SM101 (a transformable derivative of food poisoning isolate NCTC 8798) confirmed that CPE expression is required for CPE-positive, type A food poisoning isolates to cause GI effects in animal models (Sarker et al 1999). Additionally, CPE-positive type A isolates became implicated during the mid-1980s as the cause of up to 5-15% of all human nonfood-borne GI disease cases, e.g., antibiotic-associated diarrhea (AAD; Borriello et al 1984).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, this toxin is detectable in the feces of virtually all people suffering from C. perfringens type A food poisoning and human volunteer feeding studies showed that ingestion of purified CPE is sufficient to reproduce the diarrhea and cramping symptoms of the natural food poisoning [1]. Most importantly, Molecular Koch's postulate analyses showed that CPE expression is required for the enteric virulence of food poisoning isolates in rabbit ileal loops [8].…”
mentioning
confidence: 99%